(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This study focuses on cross-linguistic effects of two languages namely English and Uzbek languages. This research refers to some sources such as Rosa Alonso Alonso (2019), Ringbom, (2007, 2016), Kormos (2006) and so on. Although references are good enough, there is lack of coverage of expert audience. Overall, we can get obvious result of intercultural reflects while learning and teaching foreign language. Current study is highly needful in the field of teaching language regardless target language. It is unavoidable fact that we have to consider cultural sides of education